Performance analysis of mixed FSO-RF transmission in UAV relay communication systems - Su XU; Ji ZHANG; Yanghua DIAO; Yuanying LIU; Yi ZHANG (Dianxin kexue)
A mixed free space optical (FSO)-radio frequency (RF) transmission was studied in the multiuser unmanned aerial vehicle (UAV)-aided terrestrial network.Specifically, a novel beamforming (BF) scheme was proposed based on the available statistical channel state information (CSI), and the outage performance of the considered system was analyzed.In this mixed framework, the link between the base station and the UAV employs the FSO technology, while aerial-terrestrial links use RF technology.To achieve the space division multiple access (SDMA) in RF links.First of all, the available statistical CSI was proposed, and a novel beamforming (BF) scheme was proposed to suppress the inter-user interference so that all the users can be served simultaneously.Then, based on the assumption that the FSO and RF links follow the Gamma-Gamma fading and Nakgami-m fading respectively, an analytical expression was derived for the outage probability (OP) of the considered system.Furthermore, the asymptotical OP expression in high signal-to-noise ratio regime was presented to evaluate the achievable diversity order.Finally, numerical results were given to confirm the validity of our theoretical analysis and the superiority of the proposed scheme.